Macroergonomics for Manufacturing Systems An Evaluation Approach - Realyvásquez Vargas, Arturo; Maldonado-Macias, Aide Aracely; García-Alcaraz, Jorge Luis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book introduces the main concepts of manufacturing systems and presents several evaluation approaches for these systems' evaluation. The relevant macroergonomics methods are summarized and the theoretical framework for Macroergonomic Compatibility construct is explained. This book presents a Macroergonomic Compatibility Model which proposes an instrument in the form of a Macroergonomic. The authors introduce a methodology to obtain a novel Macroergonomic Compatibility Index that enables manufacturing companies to assess and follow their progress on the implementation of macroergonomics practices.
Macroergonomics in Manufacturing Systems -- Macroergonomic Compatibility Factors -- Macroergonomic Compatibility Index for Manufacturing Systems.
Keywords: Industrial engineering; Production engineering; Industrial organization; Production management; Industrial and Production Engineering; Industrial Organization; Production